Find your balance point : clarify your priorities, simplify your life, and achieve more - Tracy, Brian; Stein, Christina Tracy (Berrett-Koehler Publishers, 2015)
Everyone today has too much to do and too little time-that's not going to change. The only way to make our lives less stressful is to make sure we spend more time doing the things that matter most and less time doing the things that matter less. When we're not clear on what is really important, we make thoughtless and impulsive choices and end up feeling exhausted and unfulfilled. Bestselling author Brian Tracy teams up with therapist Christina Stein to show how to find true balance-when all your actions and choices are guided by a profound knowledge of your deepest personal values, vision, pu.